Protocolo associativo em sessão única no tratamento da hipersensibilidade dentinária: estudo clínico, randomizado e cego - Zeni, Thayna Carolina (2022)
Dentin hypersensitivity (HD) is a frequent condition in dentistry, and is characterized by short- term acute pain caused by dentin exposure. The aim of this study was to establish a single- session associative protocol for non-restorative treatment for HD. We selected 24 individuals with HD, sensitivity level at least 4 by the Visual Analogue Scale (VAS), aged between 19 and 60 years. The study was carried out in a split-mouth manner, and each participant (n=24) had at least 1 affected tooth in all quadrants. In the four test groups, a desensitizing agent, based on 5% potassium nitrate, was used before the obliterating agent and divided into 4 groups according to the treatment protocol: Control group: universal adhesive, NDP: 5% potassium nitrate, MAP: 5% sodium fluoride and 5% potassium nitrate; RDP: light-curing varnish with S- PRG technology. After the application of the treatment protocols, the patients were reassessed immediately after, at 7, 30 and 60 days, and submitted to the sensitivity test using the VAS scale. The scores both at the established times (intra-group) and between the experimental groups (inter-group) were evaluated using the Friedman test, using a significance level of α=0.05. The results showed that the control group, NDP and MAP had a reduction in the pain score immediately after application of the product, while RDP presented pain reduction after 7 days, however, when performing the intergroup analysis, it was shown that there were no statistically significant differences for all groups. After analyzing the data, it can be concluded that all groups were efficient for the control of hypersensitivity in the 8-week evaluation.